Single-Dose Infliximab in Hepatitis C Genotype 1 Treatmentnaive Patients with High Serum Levels of Tumour Necrosis Factor-Alpha Does Not Influence the Efficacy of Pegylated Interferon Alpha-2B/Ribavirin Therapy. Issue 1 (2014) - Cooper, Curtis; Shafran, Stephen; Greenbloom, Susan; Enns, Robert; Farley, John; Hilzenrat, Nir; Williams, Kurt; Elkashab, Magdy; Abadir, Nabil; Neuman, Manuela
Abstract : BACKGROUND: Serum tumour necrosis factor-alpha (TNF-α) levels correlate negatively with hepatitis C virus (HCV) antiviral response. OBJECTIVES: To test the hypothesis that a single infliximab induction dose would positively influence on-treatment virological response and sustained virological response (SVR). METHODS: The present study was a phase IIIB, randomized, prospective, open-label pilot trial conducted at eight Canadian sites. Treatment-naive HCV genotype 1-infected patients 18 to 65 years of age with high serum TNF-α values (>300 pg/mL) were randomly assigned to receive a single pretreatment induction infliximab infusion (5 mg/kg) seven days before antiviral therapy (arm A) or no pretreatment (arm B). All patients received pegylated interferon α2b (1.5 μg/kg/week) plus weight-based ribavirin (800 mg/day to 1400 mg/day) for up to 48 weeks. RESULTS: Eighty-five patients (arm A [n=41], arm B [n=44]; 70% male) received pegylated interferon α2b. The mean age (48.1 years), race (81% white) and METAVIR fibrosis stage (F0–2 = 79%, F3–4 = 21%) were similar between groups. Infliximab was well tolerated without attributable severe adverse events; 56.5% completed the study (arm A [n=21], arm B [n=27]). Most discontinuations were due to virological failure at weeks 12 (n=20 [23.5%]) and 24 (n=7 [8.2%]) and did not differ according to group. Numerically lower proportions of infliximab recipients achieved rapid virological response (19.5% versus 36.4%), complete early virological response (43.9% versus 59.1%) and SVR (34.1% versus 52.3%). However, between-group differences did not reach statistical significance. No differences in adverse event profile or laboratory measures were noted. CONCLUSION: A single infliximab dose before pegylated-interferon α2b and ribavirin therapy did not result in greater viral decline during the first 12 weeks of HCV therapy or improved SVR.